Two new meiofaunal species of Trilobodrilus (Dinophilidae, Annelida) from California, USA - Kerbl, Alexandra; Vereide, Emilie Hernes; Gonzalez, Brett C.; Rouse, Greg W.; Worsaae, Katrine (European Journal of Taxonomy, 2018)
We describe two new species of the annelid genus Trilobodrilus Remane, 1925 (Dinophilidae Verill, 1892) from an intertidal and a subtidal location in San Diego, California. These two species show morphological and molecular divergences between each other and the previously described, geographically distant species. Intertidal T. windansea sp. nov. differs from subtidal T. ellenscrippsae sp. nov. most remarkably in the number and pattern of ciliary tufts and bands on the prostomium and along the body length, besides showing ca 15% difference in gene fragments of COI and CytB. Trilobodrilus windansea sp. nov., though nesting with T. ellenscrippsae sp. nov. in the molecular phylogenetic analyses, morphologically resembles the Japanese T. itoi Kajihara, Ikoma, Yamasaki & Hiruta, 2015 most closely, but still differs from this species in the higher number of apical ciliary tufts, an additional ciliary row posterior to the second ciliary band, and by lacking a forth ciliary band and segmentally arranged lateral ciliary tufts. Trilobodrilus ellenscrippsae sp. nov. is morphologically most similar to the Japanese T. nipponicus Uchida & Okuda, 1943, but is much shorter, has more apical ciliary tufts, and less regularly arranged lateral ciliary tufts along the body. All species differ significantly in all compared gene fragments, and no obvious correlation was found between habitat and the species morphology or relationships.